(untitled) (Analele Universității București.Filosofie, 2024)
If we accept that Kandinsky developed a systematic theory of the fundamentals of painting, we must ask what is the central concept underlying this attempt. This paper argues for the thesis that objectless vibration plays a central role in the reconstruction proposed Kandinsky’s first book, On the Spiritual in Art. This kind of vibration includes as a virtual field both shapes, sounds and colors. All these “fall” in an organized way from the virtual vibrations, and the purpose of abstract painting is to lift the mind beyond the specific distinctions of the visible world of objects to the abstract level of primordial vibrations. The article examines the origin, functions, and the effect this concept has on color theory.